SOVEREIGNTY OF LIBERALISM IN ANTHONY DOEER’S NOVEL “ALL THE LIGHT WE CANNOT SEE” (2014) - Maharani Deta Putri; Kurnia Ningsih; An Fauzia Rozani Syafei (Universitas Negeri Padang, 2018)
This study analyses the Anthony Doeers' All The Light We Cannot See (2014). This research raises the issue of sovereignty given by liberal ideology. The purpose of this research describes sovereignty that can be seen from two aspects: personal liberty and social liberty. Literature elements, such as character, conflict and setting are used in this analysis. This research analysis uses text and context based interpretation. These elements contribute to describe the extent to which character shows individual freedom and social freedom given by liberalism ideology. This study is associated with the concept of Liberalism by Leonard trewlawny Hobhouse. The results of the analysis show that even though the character has shortcomings but through the liberal understanding given, the character is able to work like normal people and inspire others.